Alkali Modification: An Approach to Improve Surface Properties of Biochar From Easily Available Feedstocks (Dhaka University Journal of Biological Sciences, 2023)
Biochar is a stable carbon-rich material whose potentials can be greatly enhanced by modification with simple treatments. Easily available two different biochars such as rice stubble biochar (RSB) and saw dust biochar (SDB) were slowly pyrolyzed (450±50°C) and modified with KOH as RSB-M and SDB-M respectively. Represented biochars were analyzed to know their physicochemical characteristics and nutrient contents. Results revealed that nutrient contents such as total N, P and S of RSB and SDB were found maximum whereas RSB-M and SDB-M showed the lowest nutrient contents. All the biochars possessed pH value higher than 7. In case of organic C, the values of RSB-M (19.97%) and SDBM (17.83%) were the highest and RSB (17.32%) and SDB (14.80%) were the lowest. All the biochars showed very low concentration of heavy metals (such as Cr, Cd, Pb and Ni). Water holding capacity, average particle size and surface area were higher in the RSB-M and SDB-M compared to unmodified RSB and SDB. These findings showed that alkali-modified biochars had better surface properties than unmodified biochars.Dhaka Univ. J. Biol. Sci. 31(2): 213-223, 2022 (July)